Learning Activities of Indonesian Language Content Using The Project Based Learning Model - Rossy Arlinda; Iriani Bakti; Norestawati Norestawati (Vidya Karya, 2023)
The purpose of this study was to determine teacher and student activities as well as to improve student learning outcomes. This research used Classroom Action Research (CAR). This research was conducted in two cycles. This research was conducted in class IV-A of SDN Melayu 2 with 22 students. The data were analyzed qualitatively, namely teacher and student activities, and quantitatively, namely student learning outcomes. The data generated from the instrument sheet, observation sheets and learning outcomes tests were then analyzed using descriptive techniques and described in the form of tables and graphs, then students understood using the criteria for each indicator of the achievement of teacher activities and activities, as well as the achievement of mastery learning and individually classic. The study's findings showed that the teacher's activity in cycle 1 obtained a score of 19 "Good" criteria, increasing in cycle 2 to 22 with "Very Good" criteria. Student activity also increased in cycle 1, obtaining 55% with the criteria of "Enough Active" and increased in cycle 2 to 86% with the "Very Active" criteria. Likewise, student learning outcomes in cycle 1 obtained 64% of students who completed and increased in cycle 2 to 86% of students who completed. Based on the results of this study, there was an increase in teacher activities, students’ activities, and learning outcomes.